Symbolic analysis of heart rate variability during exposure to musical auditory stimulation - Vanderlei, Franciele Marques [UNESP]; de Abreu, Luiz Carlos; Garner, David Matthew; Valenti, Vitor Engrácia [UNESP] (My University, 2016)
Background • In recent years, the application of nonlinear methods for analysis of heart rate variability (HRV) has increased. However, studies on the influence of music on cardiac autonomic modulation in those circumstances are rare. Objective • The research team aimed to evaluate the acute effects on HRV of selected auditory stimulation by 2 musical styles, measuring the results using nonlinear methods of analysis: Shannon entropy, symbolic analysis, and correlation-dimension analysis. Design • Prospective control study in which the volunteers were exposed to music and variables were compared between control (no auditory stimulation) and during exposure to music. Setting • All procedures were performed in a soundproofed room at the Faculty of Science and Technology at São Paulo State University (UNESP), São Paulo, Brazil. Participants • Participants were 22 healthy female students, aged between 18 and 30 y. Intervention • Prior to the actual intervention, the participants remained at rest for 20 min, and then they were exposed to one of the selected types of music, either classical baroque (64-84 dB) or heavy-metal (75-84 dB). Each musical session lasted a total of 5 min and 15 s. At a point occurring up to 1 wk after that day, the participants listened to the second type of music. The 2 types of music were delivered in a random sequence that depended on the group to which the participant was assigned. Outcome Measures • The study analyzed the following HRV indices through Shannon entropy; symbolic analysis—0V%, 1V%, 2LV%, and 2ULV%; and correlationdimension analysis. Results • During exposure to auditory stimulation by heavy-metal or classical baroque music, the study established no statistically significant variations regarding the indices for the Shannon entropy; the symbolic analysis—0V%, 1V%, and 2ULV%; and the correlationdimension analysis. However, during heavy-metal music, the 2LV% index in the symbolic analysis was reduced compared with the controls. Conclusions • Auditory stimulation with the heavy-metal music reduced the parasympathetic modulation of HRV, whereas no significant changes occurred in cardiac autonomic modulation during exposure to the classical music.